Hydrocephalus - a typical radiological symptom? - Marta Marek; Agata Aleksandra Macionga; Kinga Szopińska; Ewa Kluczewska (Śląski Uniwersytet Medyczny w Katowicach, 2023)
Hydrocephalus can have many causes. The task of a radiologist in addition to find out about enlargement of the ventricular system by using diagnostic imaging methods is also to attempt to determine the cause of such a condition. The authors would like to present the subject of the formation of and issues related to the disturbance of cerebrospinal fluid circulation. The aim of the study was also to present the current classification of hydrocephalus in order to facilitate communication between physicians - the radiologist and neurologist. It is important to draw the attention of radiologists to the fact that hydrocephalus is not only a radiological symptom, but may also be associated with disturbances in the clinical picture of patients affected by hydrocephalus.